Your next boss is American: Attitudes of South African managers towards prospective US-South African joint ventures - W. A. Akande; M. Banai (South African Journal of Business Management, 2009)
This study explores South African managers' expectations of prospective South African – United States international joint ventures. One hundred and three middle-level South African managers responded to a theory-based original survey questionnaire that included questions about various aspects of prospective US-South African joint ventures. US companies invest in South Africa to gain access to its market and South African companies get into joint ventures with US companies to tap into their financial resources. Tarrifs imposed by the US government and the South African government's administrative barriers seem to be the most crucial problems for the prospective joint ventures. Implications for international managers are offered.
Keywords: 650